The Notion of «Transitivity» from the 4th Century BC to the 6th Century AD: the Formation of the Category - Manzano Ventura, Victoria (Cuadernos de Filología Clásica. Estudios Latinos, 2020)
This study establishes, in a systematic way, the genesis and formation process of the notion of transitivity, from the first embryonic notes of the concept in Greek philosophy to its extension and development in the fundamental and influential work of Priscian Institutiones grammaticae, at the end of the first quarter of the 6th century. The research outlines the dependencies and debts of the preceding period for each stage and author studied, as well as the original contributions that had the greatest subsequent impact. Likewise, the contradictions and difficulties in delimiting and interpreting the concept are highlighted in the different works and texts analysed; difficulties which are, without a doubt, the root of many problems associated with the phenomenon of transitivity in modern linguistics.
Keywords: Transitivity; genesis; formation process; 4th century BC - 6th century AD; heritage; innovation